PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP ENTERPRISE RISK MANAGEMENT DISCLOSURE DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR TAHUN 2015 – 2019) - Karo Karo Rama Ary; Efni Yulia; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Risk is always associated with uncertainty. In doing business, risk is something that is very much feared. Risk is something uncertain that can affect the future in the process of achieving goals. Today's perceptions of risk have changed. In the past, risk was viewed negatively, whereas now, risk is viewed both positively and negatively in response to the outcome of a number of events. This study aims to determine the effect of ownership structure, leverage and company size on enterprise risk management disclosure with good corporate governance as a moderating variable in a company. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2015-2019. The sample of this research is 175 of 235 manufacturing companies listed on the Indonesia Stock Exchange (BEI). This sample was selected using purposive sampling criteria. To determine the effect of ownership structure, leverage and company size on enterprise risk management disclosure with good corporate governance as a moderating variable, this study used descriptive statistical analysis. The results of the study state that: managerial ownership has a significant positive effect on enterprise risk management disclosure, institutional ownership has a negative and insignificant effect on enterprise risk management disclosure, positive leverage has a significant effect on enterprise risk management disclosure, firm size has a significant negative effect on enterprise risk management disclosure. risk management disclosure, good corporate governance has a significant positive effect on enterprise risk management disclosure, good corporate governance is able to moderate the effect of managerial ownership on enterprise risk management disclosure, good corporate governance is able to moderate the effect of institutional ownership on enterprise risk management disclosure, good corporate governance is not able to moderate the effect of leverage on enterprise risk management disclosure, good corporate governance is not able to moderate the influence the size of the company against the enterprise risk management disclosure.Keywords: Managerial Ownership, Institutional Ownership, Leverage, Company Size, Enterprise Risk Management Disclosure and Good Corporate Governance.